Meet Japan : - Hibino, Tsuneji (Charles E. Tuttle Co., 1968)
This book's audience is sure to be wide and varied as it is highly suitable as a school textbook, excellent background for the businessman or tourist, and interesting reading for all those who wish concise but ac-curate knowledge of the foremost country in Asia.